LSP-SPP Coupling Structure Based on Three-Dimensional Patterned Sapphire Substrate for Surface Enhanced Raman Scattering Sensing - Xie, Shuqi; Si, Haipeng; Liu, Cong; Liu, Weihao; Shafi, Muhammad; Jiang, Shouzhen; Yue, Weiwei (Nanomaterials (Basel, Switzerland), 2023)
Although the fabrication of controllable three-dimensional (3D) microstructures on substrates has been proposed as an effective solution for SERS, there remains a gap in the detection and manufacturability of 3D substrates with high performance. In this study, photolithography is adopted to obtain a pyramid-like array on a patterned sapphire substrate (PSS), with Al2O3 as the dielectric layer. In addition, silver nanoparticles (AgNPs) are used to decorate Au films to obtain mass-producible 3D SRES substrates. In the case of low fluorescence, the substrate realizes the coupling of localized surface plasmon polaritons (LSPs) and surface plasmon polaritons (SPPs), which is consistent with the simulation results obtained using the finite element method. The performance of the SERS substrate is evaluated using rhodamine 6G (R6G) and toluidine blue (TB) as probe molecules with detection limits of 10−11 M and 10−9 M, respectively. The substrate exhibits high hydrophobicity and excellent light-capturing capability. Moreover, it shows self-cleaning ability and long-term stability in practical applications. Allowing for the consistency of the composite substrate in the preparation process and the high reproducibility of the test results, it is considered to be promising for mass production.